ANALYSIS OF ADULT DIETARY HABITS AND NUTRITIONAL WELL-BEING IN UMUAHIA METROPOLIS: IMPLICATIONS FOR EDUCATIONAL PRACTICE, COMMUNITY HEALTH, EDUCATIONAL MANAGEMENT, AND COUNSELLING SERVICES - Michael, Onwumere; Melody, Modebelu N.; Obande-Ognuinya, Nkiru Edith; Kelechi, David Onyemaechi Ekeh; Mezieobi, Kelechi Chinemerem; Omogo, Peter Okwoeze; Vitalis, Mpamugo Onyebuchi; A., Uchendu Ijeoma; C. , Ojemuyide Chidiebere; Ada, Alo Chinyere; Otozi, Edwin Idenyi; Ezeoke, Ngele Cletus; et al. (Veredas do Direito, 2026)
This study employed a cross-sectional survey design to investigate the Adult Dietary Habits and Nutritional Well-Being in Umuahia Metropolis, with its implications for Educational Practice, Community Health, Educational Management, and Counselling Services.. A multistage sampling technique was utilized, where the city was first divided into clusters based on the total number of wards. Out of 22 wards in Umuahia Metropolis, 9 wards (4 wards from Umuahia South and 5 wards from Umuahia North) were randomly selected using a table of random numbers. From these 9 wards, a total of 360 households were selected, with 40 households chosen from each ward using a systematic sampling technique. Data on dietary habits were collected using the World Health Organization's standard questionnaire on dietary assessment, which was adapted and validated for the study population. Statistical analysis was performed using SPSS version 22.0, with descriptive statistics and inferential statistics used to analyze the data. The study revealed a higher proportion of females (54.0%) than males (46.0%), with most respondents (89.2%) being young and middle-aged adults (20-59 years). The key findings included, among others, 39.4% of respondents consumed home-prepared meals at work or market, with 44.2% doing so occasionally, 31.4% and 22.3% of respondents consumed snacks and sweetened beverages 3-7 times weekly, respectively, 94% of respondents skipped one or more meals per day, high consumption of oil-rich foods (96.8%) and spices/beverages (100%) was observed, while vegetable consumption was high (94.8%), and fruit consumption was relatively low (27.8%). Based on the findings, the study recommended among others that nutrition stakeholders create awareness and promote healthy food choices in Umuahia Metropolis, given the unhealthy dietary habits observed.